Rare earth modified manganese-containing corrosion-resistant high-entropy alloy and preparation method thereof
By optimizing the smelting process of high-entropy alloy, Mn elements are melted in two steps and using rare earth elements to adsorb O and S, forming rare earth inclusions with stronger corrosion resistance, solving the problem of uneven composition of high-entropy alloys and improving the alloy Corrosion resistance and mechanical properties reduce material costs.
Patent Information
- Application Number
- CN202411293084.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-14
AI Technical Summary
It is difficult to control the uniformity of components during the smelting process, resulting in poor performance, especially the volatile nature of rare earth elements and the high melting point of oxides, which makes the material components uneven, affecting its corrosion resistance and mechanical properties.
By optimizing the smelting process, Mn elements and other elements are melted in two steps, and rare earth elements are used to adsorb O and S elements to form rare earth inclusions with stronger corrosion resistance, improve the performance of the passivation film, and improve the corrosion resistance of the alloy.
It achieves better pitting resistance and passivation film protection, inhibits the formation of MnS and MnCr2O4 inclusions, significantly improves the corrosion resistance of the alloy, and reduces material costs.
Smart Images

Figure CN119243008A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a rare earth modified manganese-containing corrosion-resistant high-entropy alloy and a preparation method thereof, belonging to the technical field of high-entropy alloy smelting. Background Art
[0002] When traditional materials are in service in special fields, their mechanical properties or corrosion resistance often fail to meet the harsh service environment, thus affecting the long-term stability and safety of the engineering structure, and directly affecting the service life and maintenance cost of the material. In order to solve this problem, high entropy alloys came into being. With their stable high mixed entropy and solid solution structure, high entropy alloys have broken through the limitations of traditional alloys and greatly expanded the possibilities of alloy design. High entropy alloys exhibit excellent comprehensive mechanical properties, corrosion resistance, and wear resistance, and are strong candidates for the research and development of special equipment.
[0003] Rare earth elements are known as "industrial vitamins". Rare earth microalloying can refine the grain size of materials or form second-phase particles, and can also change the electrochemical properties of alloys and form a denser oxide film on the surface of alloys. It is an effective method to improve the mechanical properties and corrosion resistance of materials at the same time. This makes rare earth elements have important application value in the design and manufacture of advanced materials, and they are widely used in steel, magnesium alloys and aluminum alloys.
[0004] However, due to the volatility of rare earth elements and the high melting point of rare earth oxides, it is difficult to control the uniformity of the composition during the smelting process, resulting in uneven composition of the material and poor performance. Therefore, controlling the volatilization of rare earth elements and the uniformity of the ingot during the smelting process is of great significance to the preparation of high entropy alloys. Summary of the invention
[0005] The present invention aims to provide a rare earth modified manganese-containing corrosion-resistant high-entropy alloy and a preparation method thereof. By optimizing the smelting process, the problem that it is difficult to control the uniformity of the components of the high-entropy alloy during the smelting process, resulting in poor alloy performance, is solved. The obtained alloy has better pitting resistance and passivation film protection.
[0006] At present, doping with rare earth is an effective method to improve the corrosion resistance of materials. Among the rare earth elements, Ce and Y are common rare earth elements, and the prices of these two elements are relatively low, which has certain economical efficiency. The doping of trace rare earth elements will not change the original single-phase structure of high entropy alloys. In addition, in the present invention, the purpose of adding Mn and Cr elements is to improve the mechanical properties of the alloy, but due to the easy formation of MnS and MnCr inside the alloy, the alloy will be more easily broken. 2 O 4Inclusions lead to segregation of Cr and pitting of MnS, making the corrosion resistance of the alloy poor. The addition of rare earth elements can adsorb O and S elements and exclude Mn and Cr elements, making the elements inside the material more uniform and forming rare earth inclusions with stronger corrosion resistance, thereby improving the performance of the passivation film and effectively improving the corrosion resistance of the alloy.
[0007] The reason why the content of rare earth elements selected in the present invention is 0.01~0.5 at.% is that due to the limited solid solubility of rare earth elements in the material, its content is usually within 0.5 at.%, because excessive rare earth elements will lead to an increase in inclusions and defects in the material, significantly reduce the plasticity of the material, and increase the cost.
[0008] The invention provides a rare earth modified manganese-containing corrosion-resistant high-entropy alloy, which is composed of Fe, Mn, Cr, Ni and RE, wherein RE includes Ce or Y, wherein the atomic ratio of RE to the sum of the other four elements is x: (100-x), wherein x is 0.01-0.5; the atomic ratio of the other four elements Fe, Mn, Cr and Ni is: 40:20:20:20.
[0009] Furthermore, the elements selected for the high entropy alloy are all bulk raw materials with a purity greater than 99.95%.
[0010] The present invention provides a method for preparing the above-mentioned Fe-Mn-Cr-Ni-RE high entropy alloy, which specifically comprises the following steps: S1. Weigh the raw materials according to the chemical composition and atomic ratio of the high entropy alloy, then grind the oxide scale and perform ultrasonic cleaning in alcohol to remove impurities; S2, dividing the raw materials prepared in step S1 into two parts, the first part includes Fe, Cr, Ni and RE elements, and the second part contains only pure Mn single element, and the two parts of raw materials are respectively placed in two copper crucibles of an electric arc furnace; S3, use the mechanical pump to evacuate the air and then start the molecular pump to continue evacuating the air to 1×10 -3 Pa~3×10 -3 Pa, then close the valve and molecular pump; fill with high-purity argon gas to make the pressure in the furnace 0.3-0.5atm; S4, turn on the welding current and voltage, heat and melt the sponge titanium block after the arc is struck, observe the surface color after the titanium block cools down, if the surface still shows a silvery white metallic luster, it proves that there is no air remaining in the furnace chamber; then melt the Fe, Cr, Ni, and RE raw materials placed in step S2; S5, using a tool to move the ingot obtained in step S4 into a crucible containing raw material Mn, and continue smelting; S6, sucking the melted ingot in step S5 into a mold of 85 mm×10 mm×6 mm, cooling for 10 to 20 minutes, opening the mold and taking out the sample; S7. heat-treating the obtained sample.
[0011] Furthermore, in step S1, since the melting point of the Mn element is relatively low and it is volatile, 1% to 5% more Mn needs to be weighed during the preparation to compensate for it.
[0012] Further, in step S2, the first batch of raw materials are placed in a copper crucible in the order of Ni, Fe, RE, and Cr from bottom to top, and RE is wrapped by the other three raw materials.
[0013] Further, in step S4, the raw material is first preheated from the edge with a low fire, and then smelted evenly with a high fire for 20 to 30 seconds; the smelting is repeated 3 to 6 times, and the alloy ingot is turned over by using an auxiliary tool before each smelting.
[0014] Furthermore, in step S5, the smelting is repeated 5 to 6 times, and the alloy ingot is turned over using an auxiliary tool before each smelting.
[0015] Further, in step S7, the heat treatment process is: homogenization treatment at 1200-1300°C for 2-5h, cold rolling for 50-80%, and then recrystallization annealing at 1000-1100°C for 0.5-1h.
[0016] Beneficial effects of the present invention: (1) The present invention improves the traditional preparation method and obtains a stable Fe-Mn-Cr-Ni-RE high entropy alloy containing rare earths: the alloy obtained by the traditional preparation method causes the rare earth elements to be dissolved in the matrix or only a very small amount to be enriched in the inclusions, resulting in the inability to suppress the original inclusions such as MnS in the alloy that are unfavorable to the pitting corrosion resistance; the preparation method designed by the present invention can effectively prevent RE and Mn from being dissolved first by smelting the Mn element and the other four elements in two steps. The prepared alloy can modify the MnS inclusions into RE-OS inclusions, thereby improving the pitting corrosion potential of the material in the chloride solution, enhancing the density of the passivation film, and suppressing the occurrence of pitting corrosion; the pitting corrosion resistance is better than that of the Fe-Mn-Cr-Ni-RE high entropy alloy prepared by the traditional method; (2) The rare earth element content in the present invention is relatively low, and the main elements are all commonly used alloys, so the material cost is relatively low. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The present invention is a process flow chart for preparing the same; Figure 2 It is prepared in Example 1 of the present invention (Fe 40 Mn20 Cr 20 Ni 20 ) 99.9 Ce 0.1 Morphology and composition of inclusions in high entropy alloys; Figure 3 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Ce 0.1 High entropy alloy and Fe of comparative example 1 40 Mn 20 Cr 20 Ni 20 Polarization curves of high entropy alloys in 3.5 wt.% NaCl solution; Figure 4 It is prepared in Example 1 of the present invention (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Ce 0.1 Impedance spectrum curves of high entropy alloy and comparative example 1 and comparative example 2 in 3.5 wt.% NaCl solution; Figure 5 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1 Morphology and composition of inclusions in high entropy alloys; Figure 6 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1 Polarization curves of high entropy alloys in 3.5wt.% NaCl solution; Figure 7 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1 Impedance spectrum curve of high entropy alloy in 3.5wt.%NaCl solution; Figure 8 The (Fe 40 Mn 20 Cr20 Ni 20 ) 99.95 Ce 0.05 SEM and EDS images of alloy inclusions; Fig. 9 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.95 Ce 0.05 Potentiodynamic polarization curves of the alloy in 3.5 wt% NaCl solution. DETAILED DESCRIPTION
[0018] The present invention is further illustrated by the following examples, but is not limited to the following examples.
[0019] Comparative Example 1 The Fe mentioned in the present invention 40 Mn 20 Cr 20 Ni 20 The high entropy alloy is prepared by vacuum arc melting. During melting, Ni, Fe, Mn, and Cr are placed in the same copper crucible in the order from bottom to top, and the melting is performed six times. Before each melting, the ingot is turned over and sucked into a mold. The mold size and heat treatment process are the same as those of the present invention.
[0020] Comparative Example 2 This example is obtained by traditional process (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Ce 0.1 The high entropy alloy is prepared by vacuum arc melting, and during melting, Ni, Fe, Ce, Mn, and Cr are placed in the same copper crucible in the order from bottom to top, and the melting is performed six times, and the ingot is turned over before each melting and sucked into a mold. The heat treatment process is the same as that of the present invention.
[0021] The difference from the present invention is that the conventional process uses a single crucible and an ingot can be obtained by smelting once, while the present invention places the rare earth and other elements separately to obtain a material with better performance.
[0022] Comparative Example 3 This example is obtained by traditional process (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1The high entropy alloy is prepared by vacuum arc melting, and during melting, Ni, Fe, Y, Mn, and Cr are placed in the same copper crucible in the order from bottom to top, and the melting is performed six times, and the ingot is turned over before each melting and sucked into a mold. The heat treatment process is the same as that of the present invention.
[0023] Comparative Example 4 This example is obtained by traditional process (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.95 Ce 0.05 The high entropy alloy is prepared by vacuum arc melting, and during melting, Ni, Fe, Ce, Mn, and Cr are placed in the same copper crucible in the order from bottom to top, and the melting is performed six times, and the ingot is turned over before each melting and sucked into a mold. The heat treatment process is the same as that of the present invention. Example 1
[0024] The present embodiment is a Fe-Mn-Cr-Ni-RE series high entropy alloy, which is composed of five elements: Fe, Mn, Cr, Ni, and Ce, and the composition is (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Ce 0.1 .
[0025] The above (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Ce 0.1 A method for preparing a high entropy alloy comprises the following steps: S1. According to (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Ce 0.1 Chemical composition and mass fraction of high entropy alloys Weigh the raw materials, then grind the oxide scale and ultrasonically clean them in alcohol for 3 minutes to remove impurities. When configuring, it is necessary to weigh 5% more Mn to compensate for its volatilization.
[0026] S2, the raw materials prepared in step S1 are divided into two parts, the first part is four elements of Fe, Cr, Ni and Ce, and the second part contains only pure Mn single element, and the two parts of raw materials are placed in two copper crucibles of the electric arc furnace. The first part of raw materials is placed in the copper crucible in the order of Ni, Fe, Ce, Cr from bottom to top, and Ce is wrapped by the other three raw materials. Then close the furnace door.
[0027] S3, use the mechanical pump to evacuate the air and then start the molecular pump to continue evacuating the air to 3×10 -3 Pa, then close the valve and molecular pump. Fill with high-purity argon gas to make the pressure in the furnace 0.4atm.
[0028] S4, turn on the current and voltage, and heat and melt the titanium sponge block after arcing. After the titanium block cools down, observe the surface color. If the surface still shows a silvery white metallic luster, it proves that there is no air remaining in the furnace. Then, the first portion of Fe, Cr, Ni, and Ce raw materials placed in step S2 are melted, each melting time is 20 seconds, a total of 5 times, and the ingot is turned over before each melting.
[0029] S5. Use a tool to move the alloy ingot into the crucible containing the raw material pure Mn, and continue smelting for 6 times, each smelting for 20 seconds, and turn the ingot over before smelting.
[0030] S6. Suck-cast the molten ingot into a mold of 85 mm × 10 mm × 6 mm. After cooling for 10 minutes, open the mold and take out the sample.
[0031] S7. The obtained sample was homogenized at 1200°C for 2 h, cold rolled by 70%, and then recrystallized annealed at 1000°C for 1 h.
[0032] Figure 2 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Ce 0.1 SEM and EDS images of the alloy inclusions show that the Ce content in the inclusions is 20.45 at%, and the rest are 42.08 at% O, 9.08 at% S, 12.01 at% Fe, 5.69 at% Ni, 6.79 at% Cr and 3.90 at% Mn.
[0033] Figure 3 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Ce 0.1 From the potentiodynamic polarization curve of the alloy in 3.5wt% NaCl solution, it can be seen that the corrosion resistance of the alloy prepared in the present invention is significantly higher than that of Comparative Examples 1 and 2, and the pitting potential is increased by 190mV compared with that of Comparative Example 2.
[0034] Figure 4 The (Fe40 Mn 20 Cr 20 Ni 20 ) 99.9 Ce 0.1 From the impedance spectrum of the alloy in 3.5wt% NaCl solution, it can be seen that the arc radius of the Nyquist plot is larger than that of Comparative Examples 1 and 2. Compared with the alloys prepared in Comparative Examples 1 and 2, the passivation film thickness calculated based on the impedance spectrum is increased by 1.2nm and 0.5nm, respectively. Example 2
[0035] The present embodiment is a Fe-Mn-Cr-Ni-RE series high entropy alloy, which is composed of five elements: Fe, Mn, Cr, Ni, and Y, and the composition is (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1 .
[0036] The above (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1 A method for preparing a high entropy alloy comprises the following steps: S1. According to (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1 Chemical composition and mass fraction of high entropy alloys Weigh the raw materials, then grind the oxide scale and ultrasonically clean them in alcohol for 3 minutes to remove dust. During the configuration, 5% more Mn needs to be weighed to compensate for its volatilization.
[0037] S2, the raw materials prepared in step S1 are divided into two parts, the first part contains four elements of Fe, Cr, Ni and Y, and the second part contains only pure Mn, and the two parts of raw materials are placed in two copper crucibles of the electric arc furnace. The first part of raw materials is placed in the copper crucible in the order of Ni, Fe, Y, Cr from bottom to top, and Y is wrapped by the other three raw materials. Then close the furnace door.
[0038] S3, use the mechanical pump to evacuate the air and then start the molecular pump to continue evacuating the air to 3×10 -3 Pa, then close the valve and molecular pump. Fill with high-purity argon gas to make the pressure in the furnace 0.4atm.
[0039] S4, turn on the current and voltage, and heat and melt the titanium sponge block after arcing. After the titanium block cools down, observe the surface color. If the surface still shows a silvery white metallic luster, it proves that there is no air remaining in the furnace. Then melt the first portion of Fe, Cr, Ni, and Y raw materials placed in step S2, each melting for 20 seconds, for a total of 5 times, and turn the ingot over before each melting.
[0040] S5. Use a tool to move the alloy ingot into the crucible containing the raw material pure Mn, and continue smelting for 6 times, each smelting for 20 seconds, and turn the ingot over before smelting.
[0041] S6. Suck-cast the molten ingot into a mold of 85 mm × 10 mm × 6 mm. After cooling for 10 minutes, open the mold and take out the sample.
[0042] S7. The obtained sample was homogenized at 1200°C for 2 h, cold rolled by 70%, and then recrystallized annealed at 1000°C for 1 h.
[0043] Figure 5 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1 SEM and EDS images of the alloy inclusions show that the Y content in the inclusions is 32.4 at%, and the rest are 7.2 at% O, 40.4 at% S, 5.22 at% Fe, 2.14 at% Ni, 3.1 at% Cr and 9.54 at% Mn.
[0044] Figure 6 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1 From the potentiodynamic polarization curve of the alloy in 3.5 wt% NaCl solution, it can be seen that the corrosion resistance of the alloy prepared in the present invention is significantly higher than that of the alloy prepared in Comparative Example 3, and the pitting potential is increased by 170 mV compared with that in Comparative Example 3.
[0045] Figure 7 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.9 Y 0.1The impedance spectrum of the alloy in 3.5 wt% NaCl solution shows that the radius of the Nyquist plot arc is also larger. Compared with the alloy prepared in Comparative Example 3, the thickness of the passivation film calculated based on the impedance spectrum is increased by 0.7 nm. Example 3
[0046] The present embodiment is a Fe-Mn-Cr-Ni-RE series high entropy alloy, which is composed of five elements: Fe, Mn, Cr, Ni, and Ce, and the composition is (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.95 Ce 0.05 .
[0047] The above (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.95 Ce 0.05 A method for preparing a high entropy alloy comprises the following steps: S1. According to (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.95 Ce 0.05 Chemical composition and mass fraction of high entropy alloys Weigh the raw materials, then grind the oxide scale and ultrasonically clean them in alcohol for 3 minutes to remove impurities. When configuring, it is necessary to weigh 5% more Mn to compensate for its volatilization.
[0048] S2, the raw materials prepared in step S1 are divided into two parts, the first part is four elements of Fe, Cr, Ni and Ce, and the second part contains only pure Mn single element, and the two parts of raw materials are placed in two copper crucibles of the electric arc furnace. The first part of raw materials is placed in the copper crucible in the order of Ni, Fe, Ce, Cr from bottom to top, and Ce is wrapped by the other three raw materials. Then close the furnace door.
[0049] S3, use the mechanical pump to evacuate the air and then start the molecular pump to continue evacuating the air to 3×10 -3 Pa, then close the valve and molecular pump. Fill with high-purity argon gas to make the pressure in the furnace 0.4atm.
[0050] S4, turn on the current and voltage, and heat and melt the titanium sponge block after arcing. After the titanium block cools down, observe the surface color. If the surface still shows a silvery white metallic luster, it proves that there is no air remaining in the furnace. Then, the first portion of Fe, Cr, Ni, and Ce raw materials placed in step S2 are melted, each melting time is 20 seconds, a total of 5 times, and the ingot is turned over before each melting.
[0051] S5. Use a tool to move the alloy ingot into the crucible containing the raw material pure Mn, and continue smelting for 6 times, each smelting for 20 seconds, and turn the ingot over before smelting.
[0052] S6. Suck-cast the molten ingot into a mold of 85 mm × 10 mm × 6 mm. After cooling for 10 minutes, open the mold and take out the sample.
[0053] S7. The obtained sample was homogenized at 1200°C for 2 h, cold rolled by 70%, and then recrystallized annealed at 1000°C for 1 h.
[0054] Figure 8 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.95 Ce 0.05 The SEM and EDS images of the alloy inclusions showed that the Ce content in the inclusions was 13.52 at%, and the rest were 61.45 at% O, 0.03 at% S, 2.07 at% Fe, 0.98 at% Ni, 0.98 at% Cr and 20.97 at% Al.
[0055] Fig. 9 The (Fe 40 Mn 20 Cr 20 Ni 20 ) 99.95 Ce 0.05 From the potentiodynamic polarization curve of the alloy in 3.5 wt% NaCl solution, it can be seen that the corrosion resistance of the alloy prepared in the present invention is higher than that of Comparative Example 4, and the pitting potential is increased by 103 mV compared with that of Comparative Example 4.
Claims
1. A rare earth modified manganese-containing corrosion-resistant high entropy alloy, characterized in that: It is composed of Fe, Mn, Cr, Ni, and RE, wherein RE includes Ce or Y, and the atomic ratio of RE to the sum of the other four elements is x: (100-x), wherein x is 0.01~0.5; the atomic ratio of the other four elements Fe, Mn, Cr, and Ni is: 40:20:20:
20.
2. The rare earth modified manganese-containing corrosion-resistant high entropy alloy according to claim 1, characterized in that: The elements selected for the high entropy alloy are all bulk raw materials with a purity greater than 99.95%.
3. A method for preparing the rare earth modified manganese-containing corrosion-resistant high entropy alloy according to claim 1 or 2, characterized in that The specific steps include: S1. Weigh the raw materials according to the chemical composition and atomic ratio of the high entropy alloy, then grind the oxide scale and perform ultrasonic cleaning in alcohol to remove impurities; S2, dividing the raw materials prepared in step S1 into two parts, the first part includes Fe, Cr, Ni and RE elements, and the second part contains only pure Mn single element, and the two parts of raw materials are respectively placed in two copper crucibles of an electric arc furnace; S3, use the mechanical pump to evacuate the air and then start the molecular pump to continue evacuating the air to 1×10 -3 Pa~3×10 -3 Pa, then close the valve and molecular pump; fill with high-purity argon gas to make the pressure in the furnace 0.3~0.5atm; S4, turn on the welding current and voltage, heat and melt the sponge titanium block after the arc is struck, observe the surface color after the titanium block cools down, if the surface still shows a silvery white metallic luster, it proves that there is no air remaining in the furnace chamber; then melt the Fe, Cr, Ni, and RE raw materials placed in step S2; S5, using a tool to move the ingot obtained by smelting in step S4 into a crucible containing raw material Mn, and continue smelting; S6, sucking the melted ingot in step S5 into a mold of 85 mm×10 mm×6 mm, cooling for 10 to 20 minutes, opening the mold and taking out the sample; S7. heat-treating the obtained sample.
4. The method for preparing the rare earth modified manganese-containing corrosion-resistant high entropy alloy according to claim 3, characterized in that: In step S1, since the melting point of Mn element is low and it is volatile, 1% to 5% more Mn needs to be weighed during configuration to compensate for it.
5. The method for preparing the rare earth modified manganese-containing corrosion-resistant high entropy alloy according to claim 3, characterized in that: In step S2, the first batch of raw materials are placed in a copper crucible in the order of Ni, Fe, RE, and Cr from bottom to top, and RE is wrapped by the other three raw materials.
6. The method for preparing the rare earth modified manganese-containing corrosion-resistant high entropy alloy according to claim 3, characterized in that: In step S4, the raw material is first preheated from the edge with a low heat, and then smelted evenly with a high heat for 20 to 30 seconds; the smelting is repeated 3 to 6 times, and the alloy ingot is turned over by an auxiliary tool before each smelting.
7. The method for preparing the rare earth modified manganese-containing corrosion-resistant high entropy alloy according to claim 3, characterized in that: In step S5, the smelting is repeated 5 to 6 times, and the alloy ingot is turned over by using an auxiliary tool before each smelting.
8. The method for preparing the rare earth modified manganese-containing corrosion-resistant high entropy alloy according to claim 3, characterized in that: In step S7, the heat treatment process is: homogenization treatment at 1200-1300°C for 2-5h, cold rolling for 50-80%, and then recrystallization annealing at 1000-1100°C for 0.5-1h.
Citation Information
Patent Citations
Fe-Mn-Cr-Ni series high-entropy stainless steel and preparation method thereof
CN108660354A
Fe-Mn-Cr-Ni-series medium-entropy stainless steel and preparation method thereof
CN109913769A
High-corrosion-resistance non-equal-atomic-ratio high-entropy alloy and preparation method thereof
CN111172446A
Rare earth doped high-entropy alloy and preparation method and application thereof
CN117004864A
High-entropy superalloy
US20170369970A1
